High-porosity superfine light sound-absorbing and heat-insulating glass fiber cotton and preparation method thereof
Patent Information
- Application Number
- CN202611041240.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-14
- Publication Date
- 2026-10-27
AI Technical Summary
[0004]本发明的目的在于提供一种高孔隙超细轻质吸音隔热玻璃纤维棉及制备方法,旨在解决现有技术中的粘结树脂完整包覆纤维形成连续薄膜堵塞连通孔隙,同时高压压实压缩纤维交织间隙,成品孔径单一、无法构建多级梯度孔隙网络,造成吸音与隔热性能降低的技术问题
[0014]本发明的一种高孔隙超细轻质吸音隔热玻璃纤维棉及制备方法,包括二元复配超细无碱硼硅玻璃纤维基材85~92份、复合型高分子改性助剂4~9份和分散稳定助剂1~3份;并采用以下步骤:将石英砂、硼酸、纯碱、白云石与回收碎玻璃混合后送入电熔窑高温熔融澄清,玻璃熔体经铂合金漏板出丝并通过高速高温气流剪切分丝得到二元复配超细玻纤;将超细玻纤放入水洗活化槽采用稀硅烷水解液常温浸渍处理,水洗除去游离硅烷后低温烘干,在玻纤表面生成羟基活性位点;把活化完成的超细玻纤分散于去离子水中配制成玻纤浆料并低速打散分散,投入改性助剂充分搅拌混匀;将混合改性浆料经高压雾化设备喷至负压集棉网带,依靠分级负压气流分层铺放粗细玻纤形成梯度孔径三维骨架;采用分段低温柔性热压工艺对玻纤坯体分步加压升温;待热压固化后,将玻纤棉板材经风冷、标准裁切,单面喷淋有机硅乳液疏水强化并低温烘干;通过上述方式,实现了避免树脂封堵孔隙,无需高压压实即可稳定成型,有效提升材料孔隙率,能够优化吸音、隔热性能。
Smart Images

Figure CN122977683A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of thermal insulation and sound absorption materials, and in particular to a high-porosity, ultra-fine, lightweight sound-absorbing and heat-insulating glass fiber cotton and its preparation method. Background Technology
[0002] Fiberglass wool, with its advantages of being non-combustible, temperature-resistant, and cost-effective, has become the most mainstream sound-absorbing and heat-insulating substrate for building walls, vehicle cabins, and industrial units. Currently, traditional fiberglass wool is manufactured using a one-piece impregnation and high-temperature, high-pressure molding process.
[0003] However, during the traditional processing of glass fiber cotton, the bonding resin completely covers the fibers to form a continuous film that blocks the interconnected pores. At the same time, high pressure compacts and compresses the gaps between the interwoven fibers, resulting in a single pore size in the finished product and an inability to construct a multi-level gradient pore network, which reduces the sound absorption and heat insulation performance. Summary of the Invention
[0004] The purpose of this invention is to provide a high-porosity, ultra-fine, lightweight sound-absorbing and heat-insulating glass fiber cotton and its preparation method. The aim is to solve the technical problems in the prior art where the bonding resin completely covers the fibers to form a continuous film that blocks the interconnected pores, while high-pressure compaction compresses the gaps between the interwoven fibers, resulting in a single pore size in the finished product and the inability to construct a multi-level gradient pore network, which leads to a reduction in sound absorption and heat insulation performance.
[0005] To achieve the above objectives, the present invention employs a high-porosity, ultrafine, lightweight sound-absorbing and heat-insulating glass fiber cotton comprising: 85-92 parts of a binary composite ultrafine alkali-free borosilicate glass fiber substrate, 4-9 parts of a composite polymeric modifier, and 1-3 parts of a dispersion stabilizing agent. The binary composite ultrafine alkali-free borosilicate glass fiber substrate comprises ultrafine microfibers and supporting coarse fibers. The composite polymeric modifier comprises a water-based modified phenolic resin binder, a silane coupling agent, pore-regulating foaming microspheres, and a hydrophobic flame-retardant agent. The dispersion stabilizing agent comprises a nonionic polymeric dispersant and a pH buffer.
[0006] The present invention also provides a method for preparing high-porosity ultrafine lightweight sound-absorbing and heat-insulating glass fiber cotton, comprising the following steps.
[0007] In this process, quartz sand, boric acid, soda ash, dolomite and recycled crushed glass are mixed and sent to an electric melting furnace for high-temperature melting and clarification. The glass melt is then extruded through a platinum alloy spinneret and sheared and split by a high-speed, high-temperature airflow to obtain binary composite ultrafine glass fibers. The ultrafine glass fiber is placed in a water washing and activation tank and immersed in dilute silane hydrolysate at room temperature. After washing away the free silane, it is dried at low temperature to generate hydroxyl active sites on the surface of the glass fiber. The activated ultrafine glass fibers are dispersed in deionized water to prepare glass fiber slurry, and then dispersed at low speed. Modifying agents are added and the mixture is stirred thoroughly. The mixed modified slurry is sprayed onto the negative pressure cotton collection mesh belt through a high-pressure atomization device, and coarse and fine glass fibers are laid in layers by the graded negative pressure airflow to form a three-dimensional skeleton with gradient pore size. A segmented low-temperature flexible hot pressing process is used to pressurize and heat the glass fiber preform in stages. After hot pressing and curing, the fiberglass wool board is air-cooled, cut to standard size, sprayed with silicone emulsion on one side for hydrophobic reinforcement, and dried at low temperature.
[0008] Furthermore, in the step of mixing quartz sand, boric acid, soda ash, dolomite, and recycled crushed glass and then sending the mixture into an electric melting furnace for high-temperature melting and clarification, the glass melt is extruded through a platinum alloy spinneret and sheared and split into fibers by a high-speed, high-temperature airflow to obtain binary composite ultrafine glass fibers: Take quartz sand, boric acid, soda ash, dolomite and recycled crushed glass and mix them thoroughly; The mixed raw materials are fed into the electric melting furnace and melted through continuous high-temperature heating, and then kept at a high temperature for a long time to clarify them. The clarified molten glass liquid flows out at a constant speed from a platinum alloy porous baffle to form a continuous primary glass fiber bundle. Then, the fiber bundle is subjected to high-speed shearing and secondary stretching and splitting using a high-speed, high-temperature gas flow to obtain a binary composite ultrafine glass fiber with a combination of coarse and fine fibers. The formed ultrafine glass fibers are collected uniformly in the negative pressure cotton collection chamber, and the low-pressure blowing process is started at the same time to blow away the hard slag balls and impurities mixed in the fibers.
[0009] Furthermore, in the step of immersing ultrafine glass fibers in a water washing and activation tank at room temperature with a dilute silane hydrolysate, washing away free silane with water, and then drying at low temperature to generate hydroxyl active sites on the glass fiber surface: After slag removal and collection, the complete ultrafine glass fiber is sent into the water washing and activation tank. A dilute silane hydrolysate is prepared and completely submerges the glass fiber. The impregnation reaction is maintained at room temperature. After the impregnation reaction is complete, water is passed through to thoroughly wash the glass fiber, rinsing away any unbound free silane components adhering to the surface of the glass fiber. The washed ultrafine glass fibers are transferred to a drying device and dried as a whole using a low-temperature constant-temperature mode to remove the moisture remaining in the gaps between the glass fibers.
[0010] Furthermore, in the steps of dispersing the activated ultrafine glass fibers in deionized water to prepare a glass fiber slurry and dispersing it at low speed, and then adding the modifying additives and stirring thoroughly: All the ultrafine glass fibers that have undergone surface activation treatment are put into a stirring container containing deionized water. The water fully wets each fiber to form a basic glass fiber aqueous solution. Turn on the low-speed stirring equipment to continuously loosen and disperse the fiber clumps inside the aqueous solution, break up the tangled and agglomerated ultrafine glass fibers, and the fibers are dispersed in the water. Water-modified phenolic resin, silane coupling agent, pore-regulating foaming microspheres, hydrophobic flame retardant and dispersion stabilizing agent are added sequentially to a uniformly dispersed glass fiber aqueous solution according to the specified ratio. After all materials have been added, stir continuously at a constant speed for a long time to allow the glass fiber and various polymer additives to fully blend in the aqueous solution, forming a modified glass fiber slurry with uniform and stable composition.
[0011] Furthermore, in the step of spraying the mixed modified slurry onto a negative pressure cotton collecting mesh belt via a high-pressure atomization device, and relying on the graded negative pressure airflow to lay coarse and fine glass fibers in layers to form a three-dimensional skeleton with gradient pore sizes: The modified glass fiber slurry, after being mixed, is conveyed to a high-pressure atomization device, and the slurry is evenly sprayed onto the surface of a continuously operating negative pressure cotton collection mesh belt through the atomization nozzle; The graded negative pressure system is activated, and the fibers are laid in layers by airflow with different negative pressure intensities. The bottom layer relies on the deposition of coarse fibers to build a rigid skeleton with high negative pressure, and the surface layer relies on the deposition of ultrafine fibers with low negative pressure, naturally forming a three-dimensional fiber interwoven skeleton with gradient pore size. Low-pressure hot air is continuously blown into the newly formed fiber preform to carry out pre-drying treatment. The low-pressure hot air gradually evaporates and removes the free moisture attached to the surface of the fiber preform.
[0012] Furthermore, in the step-by-step pressurization and heating process of the glass fiber preform using a segmented low-temperature flexible hot pressing technique: The pre-dried fiber preform is fed into a hot pressing device. The first stage uses low temperature and low pressure for light hot pressing, and the foamed microspheres inside the preform expand when heated. Adjust the temperature and pressure parameters of the hot press equipment to enter the second curing process, maintain a constant temperature environment, and allow the resin in the slurry to undergo a cross-linking reaction; By controlling the hot pressing pressure and heating time, the resin at the points where the two fibers cross each other is cured and bonded into a sheet. The hot pressing equipment is equipped with a breathable steel belt, which allows moisture inside the billet to be freely discharged through the steel belt during the pressing process.
[0013] Furthermore, after the heat-pressing curing process, the fiberglass wool board is air-cooled, standard-cut, and then sprayed with hydrophobic silicone emulsion on one side for reinforcement and dried at low temperature: After the fiberglass wool board has been hot-pressed and cross-linked cured, it is taken out of the equipment and cooled naturally by air at room temperature. After cooling, it is cut into boards of uniform specifications according to the usage standards. A low-concentration silicone emulsion is evenly sprayed on one side of the cut board to complete the hydrophobic strengthening modification, and then the board is sent to a low-temperature drying equipment to dry the emulsion on the board surface. Completed glass fiber wool products were sampled in batches for full performance testing, including porosity, sound absorption coefficient, thermal conductivity and bulk density. Finished products that meet all testing standards are classified and stored in the warehouse, while substandard boards are recycled and the raw materials are sent to the front-end melting process for remelting and reuse.
[0014] This invention discloses a high-porosity, ultrafine, lightweight sound-absorbing and heat-insulating glass fiber cotton and its preparation method, comprising 85-92 parts of a binary composite ultrafine alkali-free borosilicate glass fiber substrate, 4-9 parts of a composite polymer modifier, and 1-3 parts of a dispersion stabilizing agent; and employing the following steps: mixing quartz sand, boric acid, soda ash, dolomite, and recycled crushed glass, then sending the mixture into an electric melting furnace for high-temperature melting and clarification; the glass melt is extruded through a platinum alloy perforator and sheared and split through a high-speed, high-temperature airflow to obtain binary composite ultrafine glass fibers; the ultrafine glass fibers are placed in a water washing and activation tank and impregnated at room temperature with a dilute silane hydrolysate; after washing to remove free silane, the fibers are dried at low temperature, generating hydroxyl active sites on the glass fiber surface; and then... The activated ultrafine glass fibers are dispersed in deionized water to prepare a glass fiber slurry, which is then dispersed at low speed. Modifying agents are added and the mixture is thoroughly stirred. The mixed modified slurry is sprayed onto a negative pressure cotton collection mesh belt through a high-pressure atomization device. Coarse and fine glass fibers are laid in layers by a graded negative pressure airflow to form a three-dimensional skeleton with gradient pore sizes. A segmented low-temperature flexible hot pressing process is used to pressurize and heat the glass fiber blank step by step. After hot pressing and curing, the glass fiber cotton board is air-cooled, cut to standard, sprayed with hydrophobic silicone emulsion on one side for reinforcement, and dried at low temperature. Through the above methods, the resin blockage of pores is avoided, and stable molding is achieved without high-pressure compaction, which effectively improves the porosity of the material and optimizes the sound absorption and heat insulation performance. Attached Figure Description
[0015] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0016] Figure 1 This is a flowchart of the preparation method of the high-porosity ultrafine lightweight sound-absorbing and heat-insulating glass fiber cotton of the present invention.
[0017] Figure 2 This is a flowchart of steps S100 of the present invention.
[0018] Figure 3 This is a flowchart of steps S200 of the present invention.
[0019] Figure 4 This is a flowchart of steps S300 of the present invention.
[0020] Figure 5 This is a flowchart of steps S400 of the present invention.
[0021] Figure 6 This is a flowchart of steps S500 of the present invention.
[0022] Figure 7 This is a flowchart of steps S600 of the present invention. Detailed Implementation
[0023] Exemplary embodiments will now be described in detail, examples of which are illustrated in the accompanying drawings. When the following description relates to the drawings, unless otherwise indicated, the same numbers in different drawings represent the same or similar elements. The embodiments described in the following exemplary embodiments do not represent all embodiments consistent with this application.
[0024] The terminology used in this application is for the purpose of describing particular embodiments only and is not intended to be limiting of the application. The singular forms “a,” “the,” and “the” used in this application and the appended claims are also intended to include the plural forms unless the context clearly indicates otherwise. It should also be understood that the term “and / or” as used herein refers to and includes any or all possible combinations of one or more of the associated listed items.
[0025] It should be understood that although the terms first, second, third, etc., may be used in this application to describe various information, such information should not be limited to these terms. These terms are only used to distinguish information of the same type from one another. For example, without departing from the scope of this application, first information may also be referred to as second information, and similarly, second information may also be referred to as first information. Depending on the context, the word "if" as used herein may be interpreted as "when," "when," or "in response to determination."
[0026] This invention provides a high-porosity, ultra-fine, lightweight sound-absorbing and heat-insulating glass fiber cotton, which is prepared from the following raw materials in parts by weight: The binary composite ultrafine alkali-free borosilicate glass fiber substrate consists of 85-92 parts, a composite polymer modifier of 4-9 parts, and a dispersion and stabilizing agent of 1-3 parts. The binary composite ultrafine alkali-free borosilicate glass fiber substrate includes ultrafine microfibers and supporting coarse fibers. The composite polymer modifier includes water-based modified phenolic resin binder, silane coupling agent, pore-regulating foaming microspheres, and hydrophobic flame retardant. The dispersion and stabilizing agent includes nonionic polymer dispersant and pH buffer.
[0027] Please see Figures 1-7 The present invention also provides a method for preparing high-porosity ultrafine lightweight sound-absorbing and heat-insulating glass fiber cotton, comprising the following steps: S100: Quartz sand, boric acid, soda ash, dolomite and recycled crushed glass are mixed and sent to an electric melting furnace for high-temperature melting and clarification. The glass melt is then extruded through a platinum alloy spinneret and sheared and split by a high-speed, high-temperature airflow to obtain binary composite ultrafine glass fibers.
[0028] In this embodiment, quartz sand, boric acid, soda ash, dolomite, and recycled crushed glass are mixed and then fed into an electric melting furnace for high-temperature melting and clarification. The molten glass is then extruded through a platinum alloy spinneret and sheared and split by a high-speed, high-temperature airflow to obtain binary composite ultrafine glass fibers. The specific process is as follows: S101: Take quartz sand, boric acid, soda ash, dolomite and recycled crushed glass and mix them thoroughly; S102: The mixed raw materials are fed into the electric melting furnace and melted through continuous high-temperature heating, and then kept at a high temperature for a long time to clarify. S103: The clarified molten glass liquid flows out at a constant speed from the platinum alloy porous baffle to form a continuous primary glass fiber bundle. Then, the fiber bundle is subjected to high-speed shearing and secondary stretching and splitting using a high-speed, high-temperature gas flow to obtain a binary composite ultrafine glass fiber with a combination of coarse and fine fibers. S104: The formed ultrafine glass fibers are collected uniformly in the negative pressure cotton collection chamber, and the low-pressure blowing process is started at the same time to blow away the hard slag balls and impurities mixed in the fibers.
[0029] In the above process, quartz sand, boric acid, soda ash, dolomite, and recycled crushed glass are thoroughly mixed according to the alkali-free borosilicate glass ratio to ensure uniform mixing of all solid raw materials without local segregation. The mixed raw materials are then fed into an electric melting furnace and melted under continuous high-temperature heating, followed by prolonged heat preservation and clarification to completely eliminate air bubbles trapped within the molten glass, ensuring a uniform melt texture. The clarified molten glass is then uniformly discharged from a platinum alloy porous baffle, forming a continuous primary glass fiber bundle. High-speed, high-temperature gas flow is used to shear and secondary draw the fiber bundles, resulting in a binary composite ultrafine glass fiber with a mix of coarse and fine fibers. The formed ultrafine glass fiber is then collected uniformly in a negative pressure collection chamber, while a low-pressure blowing process is simultaneously initiated to remove hard slag balls and impurities embedded in the fibers, reducing the slag ball content in the finished product. Through the above process of high-temperature melting of ore raw materials, airflow drawing into fibers, and impurity removal and purification, a binary composite ultrafine glass fiber with uniform structure and low impurity content is prepared, serving as the basic skeleton material for sound-absorbing and heat-insulating cotton.
[0030] S200: The ultra-fine glass fiber is placed in a water washing and activation tank and immersed in dilute silane hydrolysate at room temperature. After washing away the free silane, it is dried at low temperature to generate hydroxyl active sites on the surface of the glass fiber.
[0031] In this embodiment, the ultrafine glass fiber is immersed in a water washing and activation tank and treated with dilute silane hydrolysate at room temperature. After washing to remove free silane, it is dried at low temperature to generate hydroxyl active sites on the glass fiber surface. The specific process is as follows: S201: The complete ultrafine glass fiber after slag removal and collection is sent into the water washing and activation tank, and the glass fiber is completely immersed in the prepared dilute silane hydrolysis solution. The immersion reaction is maintained at room temperature. S202: After the impregnation reaction is completed, rinse the glass fiber thoroughly with clean water to remove any unbound free silane components adhering to the surface of the glass fiber. S203: The washed ultrafine glass fiber is transferred to a drying device and dried as a whole using a low-temperature constant temperature mode to remove the moisture remaining in the gaps between the glass fiber fibers.
[0032] In the above process, the intact ultrafine glass fibers, after slag removal and collection, are sent into a water washing and activation tank. A diluted silane hydrolysate is prepared and completely submerges the glass fibers. The impregnation reaction is maintained at room temperature to ensure that the silane substances fully contact the glass fiber surface. After the impregnation reaction is completed, clean water is introduced to thoroughly wash the glass fibers, rinsing away any adhering or unbonded free silane components on the glass fiber surface to prevent excess silane from accumulating and clogging the fiber gaps. The washed ultrafine glass fibers are then transferred to a drying device and dried as a whole using a low-temperature constant-temperature mode to remove any remaining moisture from the glass fiber gaps. After the complete treatment of silane impregnation, water washing, and low-temperature drying, hydroxyl active sites are stably generated on the outer wall of the glass fibers, improving the subsequent bonding ability between the polymer resin and the glass fiber interface. In this process, the surface activation modification of the glass fibers is completed, forming only a small number of active binding sites on the fiber surface without forming a thick covering layer, thus avoiding the problem of adhesive coatings clogging the fiber pores from the source.
[0033] S300: Disperse the activated ultrafine glass fibers in deionized water to prepare glass fiber slurry, disperse it at low speed, add the modifier and stir thoroughly.
[0034] In this embodiment, the activated ultrafine glass fibers are dispersed in deionized water to prepare a glass fiber slurry, which is then dispersed at low speed. Modifying agents are added and the mixture is thoroughly stirred and mixed. The specific process is as follows: S301: All the ultrafine glass fibers that have undergone surface activation treatment are put into a stirring container containing deionized water. The individual fibers are fully wetted by the water to form a basic glass fiber aqueous solution. S302: Turn on the low-speed stirring device to continuously dissipate and disperse the fiber clumps inside the aqueous solution, break up the tangled and agglomerated ultrafine glass fibers, and disperse the fibers in the water. S303: Add water-based modified phenolic resin, silane coupling agent, pore-regulating foaming microspheres, hydrophobic flame retardant and dispersion stabilizing agent sequentially to a uniformly dispersed glass fiber aqueous solution according to the specified ratio. S304: After all materials have been added, continue stirring at a constant speed for a long time to allow the glass fiber and various polymer additives to fully blend in the aqueous solution, forming a modified glass fiber slurry with uniform and stable composition.
[0035] In the above process, all the surface-activated ultrafine glass fibers are put into a stirring container filled with deionized water. The water fully wets each fiber to form a basic glass fiber aqueous solution. Then, a low-speed stirring device is turned on to continuously disperse the fiber clumps in the aqueous solution and break up the entangled ultrafine glass fibers, so that the fibers are dispersed in the water. Then, according to the formula, water-based modified phenolic resin, silane coupling agent, pore-regulating foaming microspheres, hydrophobic flame retardant additives, and dispersion stabilizing additives are added to the uniformly dispersed glass fiber aqueous solution in sequence. After all the materials have been added, the mixture is stirred at a constant speed for a long time to allow the glass fibers and various polymer additives to fully integrate in the aqueous solution and form a modified glass fiber slurry with uniform and stable composition.
[0036] S400: The mixed modified slurry is sprayed onto the negative pressure cotton collection mesh belt through a high-pressure atomization device, and coarse and fine glass fibers are laid in layers by the graded negative pressure airflow to form a three-dimensional skeleton with gradient pore size.
[0037] In this embodiment, the mixed modified slurry is sprayed onto a negative pressure cotton collecting mesh belt via a high-pressure atomization device. Coarse and fine glass fibers are layered and laid out using a graded negative pressure airflow to form a three-dimensional skeleton with gradient pore sizes. The specific process is as follows: S401: The modified glass fiber slurry that has been mixed is conveyed to the high-pressure atomization equipment, and the slurry is evenly sprayed onto the surface of the continuously operating negative pressure cotton collection mesh belt through the atomization nozzle; S402: The graded negative pressure system is activated, and the fibers are laid in layers by airflow with different negative pressure intensities. The bottom layer relies on the deposition of coarse fibers to build a rigid skeleton by large negative pressure, and the surface layer relies on the deposition of ultrafine fibers by low negative pressure, naturally forming a three-dimensional fiber interwoven skeleton with gradient pore size. S403: Low-pressure hot air is introduced to continuously blow on the newly formed fiber preform to carry out pre-drying treatment. The low-pressure hot air gradually evaporates and removes the free moisture attached to the surface of the fiber preform.
[0038] In the above process, the modified glass fiber slurry, after being mixed, is transported to a high-pressure atomizing device. The slurry is evenly sprayed onto the surface of a continuously operating negative pressure cotton collection mesh belt through the atomizing nozzle. Then, the graded negative pressure system is activated, and the fibers are laid in layers by airflow with different negative pressure intensities. The bottom layer relies on high negative pressure to deposit and support coarse fibers to build a rigid skeleton, while the surface layer relies on low negative pressure to deposit ultrafine fibers, naturally forming a three-dimensional fiber interwoven skeleton with gradient pore sizes. Then, low-pressure hot air is continuously blown through the newly formed fiber blank to carry out pre-drying treatment. The low-pressure hot air gradually evaporates and removes the free moisture attached to the surface of the fiber blank, preventing liquid resin from flowing into the fiber interior and closing the pores during subsequent hot pressing. In the above process, a multi-level interconnected pore blank structure with both macropores and mesopores is constructed in layers, widening the sound absorption band of the material. At the same time, the surface moisture is removed in advance to ensure that the pores are not blocked during subsequent hot pressing.
[0039] S500: The glass fiber preform is pressurized and heated in stages using a segmented low-temperature flexible hot pressing process.
[0040] In this embodiment, a segmented low-temperature flexible hot pressing process is used to pressurize and heat the glass fiber preform in stages. The specific process is as follows: S501: The pre-dried fiber preform is fed into a hot pressing device. The first stage uses low temperature and low pressure for light hot pressing, and the foamed microspheres inside the preform expand when heated. S502: Adjust the temperature and pressure parameters of the hot press equipment to enter the second curing process, maintain a constant temperature environment, and allow the resin in the slurry to undergo a cross-linking reaction; S503: Control the hot pressing pressure and heating time to cure and bond the resin at the points where the two fibers cross each other into a sheet. S504: The hot pressing equipment is equipped with a breathable steel belt, which allows moisture inside the billet to be freely discharged through the steel belt during the pressing process.
[0041] In the above process, the pre-dried fiber preform is fed into a hot press. The first stage uses low temperature and low pressure for mild hot pressing, causing the foamed microspheres inside the preform to expand when heated. Then, the temperature and pressure parameters of the hot press are adjusted to enter the second stage of curing, maintaining a constant temperature environment to allow the resin in the slurry to undergo a cross-linking reaction. The hot pressing pressure and heating time are then controlled so that the resin at the points where two fibers cross each other is cured and bonded into a sheet, without the overall fiber network being compacted and shrinking. Next, a breathable steel belt is provided in the hot press, allowing moisture inside the preform to be freely discharged through the steel belt during the pressing process, preventing moisture accumulation and local pore blockage. In the above, a mild segmented molding process is adopted to stabilize the fiber structure while maximizing the preservation of internal interconnected pores, taking into account both the lightweight characteristics of the finished product and stable sound absorption and heat insulation performance.
[0042] S600: After hot pressing and curing, the fiberglass wool board is air-cooled, cut to standard, sprayed with silicone emulsion on one side for hydrophobic reinforcement, and dried at low temperature.
[0043] In this embodiment, after hot pressing and curing, the fiberglass wool board is air-cooled, cut to standard size, sprayed with hydrophobic silicone emulsion on one side for reinforcement, and dried at low temperature. The specific process is as follows: S601: The fiberglass wool board that has completed hot-press cross-linking and curing is taken out of the equipment and cooled naturally by air at room temperature. After cooling, it is cut into boards of uniform specifications according to the usage standards. S602: A low-concentration silicone emulsion is evenly sprayed on one side of the cut board to complete the hydrophobic strengthening modification, and then the board surface emulsion is dried in a low-temperature drying equipment. S603: Completed glass fiber wool products are sampled in batches for full performance testing, including porosity, sound absorption coefficient, thermal conductivity and bulk density. S604: Finished products that meet all test indicators are classified and stored in the warehouse. Boards that do not meet the performance standards are uniformly recycled, and raw materials are sent to the front-end melting process for remelting and reuse.
[0044] In the above process, the fiberglass wool boards that have completed hot-press cross-linking and curing are taken out of the equipment and cooled naturally by air at room temperature. After cooling, they are cut into boards of uniform specifications according to the usage standards. Then, a low-concentration silicone emulsion is evenly sprayed on one side of the cut boards to complete the hydrophobic strengthening modification. The boards are then sent to a low-temperature drying equipment to dry the emulsion on the surface of the boards. The finished fiberglass wool products are then sampled in batches for full performance testing, including testing porosity, sound absorption coefficient, thermal conductivity, and bulk density. The finished products that meet all the test indicators are then classified and stored in the warehouse, while the boards that do not meet the performance standards are uniformly recycled. The raw materials are sent to the front-end melting process for remelting and recycling. In the above process, the hydrophobic and weather-resistant modification, standardized cutting and shaping of the products are completed. The quality of the products is controlled through full performance testing, while the unqualified raw materials are recycled and reprocessed, reducing the loss of raw materials in production.
[0045] Other embodiments of this application will readily occur to those skilled in the art upon consideration of the specification and practice of the disclosure herein. This application is intended to cover any variations, uses, or adaptations of this application that follow the general principles of this application and include common knowledge or customary techniques in the art not disclosed herein.
[0046] It should be understood that this application is not limited to the precise structure described above and shown in the accompanying drawings, and various modifications and changes can be made without departing from its scope.
Claims
1. A high-porosity, ultra-fine, lightweight sound-absorbing and heat-insulating glass fiber cotton, characterized in that, It is prepared from the following raw materials in parts by weight: The binary composite ultrafine alkali-free borosilicate glass fiber substrate consists of 85-92 parts, a composite polymer modifier of 4-9 parts, and a dispersion and stabilizing agent of 1-3 parts. The binary composite ultrafine alkali-free borosilicate glass fiber substrate includes ultrafine microfibers and supporting coarse fibers. The composite polymer modifier includes water-based modified phenolic resin binder, silane coupling agent, pore-regulating foaming microspheres, and hydrophobic flame retardant. The dispersion and stabilizing agent includes nonionic polymer dispersant and pH buffer.
2. A method for preparing high-porosity ultrafine lightweight sound-absorbing and heat-insulating glass fiber cotton, as described in claim 1, characterized in that, Includes the following steps: Quartz sand, boric acid, soda ash, dolomite and recycled crushed glass are mixed and sent to an electric melting furnace for high-temperature melting and clarification. The glass melt is then extruded through a platinum alloy spinneret and sheared and split by a high-speed, high-temperature airflow to obtain binary composite ultrafine glass fibers. The ultrafine glass fiber is placed in a water washing and activation tank and immersed in dilute silane hydrolysate at room temperature. After washing away the free silane, it is dried at low temperature to generate hydroxyl active sites on the surface of the glass fiber. The activated ultrafine glass fibers are dispersed in deionized water to prepare glass fiber slurry, and then dispersed at low speed. Modifying agents are added and the mixture is stirred thoroughly. The mixed modified slurry is sprayed onto the negative pressure cotton collection mesh belt through a high-pressure atomization device, and coarse and fine glass fibers are laid in layers by the graded negative pressure airflow to form a three-dimensional skeleton with gradient pore size. A segmented low-temperature flexible hot pressing process is used to pressurize and heat the glass fiber preform in stages. After hot pressing and curing, the fiberglass wool board is air-cooled, cut to standard size, sprayed with silicone emulsion on one side for hydrophobic reinforcement, and dried at low temperature.
3. The preparation method of high-porosity ultrafine lightweight sound-absorbing and heat-insulating glass fiber cotton as described in claim 2, characterized in that, In the process of mixing quartz sand, boric acid, soda ash, dolomite, and recycled crushed glass, and then sending the mixture into an electric melting furnace for high-temperature melting and clarification, the glass melt is extruded through a platinum alloy spinneret and sheared and split into fibers by a high-speed, high-temperature airflow to obtain binary composite ultrafine glass fibers: Take quartz sand, boric acid, soda ash, dolomite and recycled crushed glass and mix them thoroughly; The mixed raw materials are fed into the electric melting furnace and melted through continuous high-temperature heating, and then kept at a high temperature for a long time to clarify them. The clarified molten glass liquid flows out at a constant speed from a platinum alloy porous baffle to form a continuous primary glass fiber bundle. Then, the fiber bundle is subjected to high-speed shearing and secondary stretching and splitting using a high-speed, high-temperature gas flow to obtain a binary composite ultrafine glass fiber with a combination of coarse and fine fibers. The formed ultrafine glass fibers are collected uniformly in the negative pressure cotton collection chamber, and the low-pressure blowing process is started at the same time to blow away the hard slag balls and impurities mixed in the fibers.
4. The preparation method of high-porosity ultrafine lightweight sound-absorbing and heat-insulating glass fiber cotton as described in claim 2, characterized in that, In the step of immersing ultrafine glass fibers in a water washing and activation tank at room temperature with a dilute silane hydrolysate, washing away free silane with water, and then drying at low temperature to generate hydroxyl active sites on the glass fiber surface: After slag removal and collection, the complete ultrafine glass fiber is sent into the water washing and activation tank. A dilute silane hydrolysate is prepared and completely submerges the glass fiber. The impregnation reaction is maintained at room temperature. After the impregnation reaction is complete, water is passed through to thoroughly wash the glass fiber, rinsing away any unbound free silane components adhering to the surface of the glass fiber. The washed ultrafine glass fibers are transferred to a drying device and dried as a whole using a low-temperature constant-temperature mode to remove the moisture remaining in the gaps between the glass fibers.
5. The preparation method of high-porosity ultrafine lightweight sound-absorbing and heat-insulating glass fiber cotton as described in claim 2, characterized in that, In the steps of dispersing the activated ultrafine glass fibers in deionized water to prepare glass fiber slurry and dispersing it at low speed, adding the modifying additives and stirring thoroughly: All the ultrafine glass fibers that have undergone surface activation treatment are put into a stirring container containing deionized water. The water fully wets each fiber to form a basic glass fiber aqueous solution. Turn on the low-speed stirring equipment to continuously loosen and disperse the fiber clumps inside the aqueous solution, break up the tangled and agglomerated ultrafine glass fibers, and the fibers are dispersed in the water. Water-modified phenolic resin, silane coupling agent, pore-regulating foaming microspheres, hydrophobic flame retardant and dispersion stabilizing agent are added sequentially to a uniformly dispersed glass fiber aqueous solution according to the specified ratio. After all materials have been added, stir continuously at a constant speed for a long time to allow the glass fiber and various polymer additives to fully blend in the aqueous solution, forming a modified glass fiber slurry with uniform and stable composition.
6. The preparation method of high-porosity ultrafine lightweight sound-absorbing and heat-insulating glass fiber cotton as described in claim 2, characterized in that, In the step of spraying the mixed modified slurry onto the negative pressure cotton collection mesh belt through a high-pressure atomization device, and relying on the graded negative pressure airflow to lay coarse and fine glass fibers in layers to form a three-dimensional skeleton with gradient pore size: The modified glass fiber slurry, after being mixed, is conveyed to a high-pressure atomization device, and the slurry is evenly sprayed onto the surface of a continuously operating negative pressure cotton collection mesh belt through the atomization nozzle; The graded negative pressure system is activated, and the fibers are laid in layers by airflow with different negative pressure intensities. The bottom layer relies on the deposition of coarse fibers to build a rigid skeleton with high negative pressure, and the surface layer relies on the deposition of ultrafine fibers with low negative pressure, naturally forming a three-dimensional fiber interwoven skeleton with gradient pore size. Low-pressure hot air is continuously blown into the newly formed fiber preform to carry out pre-drying treatment. The low-pressure hot air gradually evaporates and removes the free moisture attached to the surface of the fiber preform.
7. The preparation method of high-porosity ultrafine lightweight sound-absorbing and heat-insulating glass fiber cotton as described in claim 2, characterized in that, In the step-by-step pressurization and heating process of the glass fiber preform using a segmented low-temperature flexible hot pressing process: The pre-dried fiber preform is fed into a hot pressing device. The first stage uses low temperature and low pressure for light hot pressing, and the foamed microspheres inside the preform expand when heated. Adjust the temperature and pressure parameters of the hot press equipment to enter the second curing process, maintain a constant temperature environment, and allow the resin in the slurry to undergo a cross-linking reaction; By controlling the hot pressing pressure and heating time, the resin at the points where the two fibers cross each other is cured and bonded into a sheet. The hot pressing equipment is equipped with a breathable steel belt, which allows moisture inside the billet to be freely discharged through the steel belt during the pressing process.
8. The preparation method of high-porosity ultrafine lightweight sound-absorbing and heat-insulating glass fiber cotton as described in claim 2, characterized in that, After heat pressing and curing, the fiberglass wool board is air-cooled, cut to standard size, sprayed with hydrophobic silicone emulsion on one side for reinforcement, and then dried at low temperature. After the fiberglass wool board has been hot-pressed and cross-linked cured, it is taken out of the equipment and cooled naturally by air at room temperature. After cooling, it is cut into boards of uniform specifications according to the usage standards. A low-concentration silicone emulsion is evenly sprayed on one side of the cut board to complete the hydrophobic strengthening modification, and then the board is sent to a low-temperature drying equipment to dry the emulsion on the board surface. Completed glass fiber wool products were sampled in batches for full performance testing, including porosity, sound absorption coefficient, thermal conductivity and bulk density. Finished products that meet all testing standards are classified and stored in the warehouse, while substandard boards are recycled and the raw materials are sent to the front-end melting process for remelting and reuse.